Impact of Partnership Business on Economic Development and Growth in Ondo State (A Study of Ondo State with Pay-Attitute Company) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Over the last two decades there has been a proliferation of partnerships between business and government, multilateral bodies and/or social actors such as NGOs and local community organizations engaged in promoting development. While proponents hail these partnerships as an important new approach to engaging business, critics argue that they are not only generally ineffective but serve to legitimate a neo-liberal, global economic order which inhibits development. This study examine impact of partnership business on economic development and growth of Ondo state through Pay-Attitute Company by assigning questionnaire to the study. The data was analyzed using descriptive statistic in line with Chi-square Technique. Three hypotheses formulated were tested using chi-square technique at 0.05(5%) level of significance. Findings disclose that ascertain ways of solving problems through effective technique has impact on growth of partnership business in Ondo State and also, partnership business has impact on the life of Ondo state citizens as shown from the result P-value (0.000